Happy Family Education Curriculum From the Perspective of Manba'ussa'adah Book by Faqihuddin Abdul Kodir - Maslahah, Siti; Idawati, Khoirotul (Pusdikra Publishing, 2024)
Family, as the primary educational institution, plays a crucial role in shaping individuals, and its harmony is essential for the well-being of all members. This study explores the concept of family education from the perspective of Faqihuddin Abdul Kodir's Manba'ussa'adah, focusing on maintaining family harmony. The research employs library research methods, utilizing two primary sources: Manba'ussa'adah by Faqihuddin Abdul Kodir and Menyelami Telaga Kebahagiaan. Data collection was conducted through documentation, and analysis was carried out using descriptive techniques. The study reveals that the curriculum for happy family education outlined in Manba'ussa'adah emphasizes providing fundamental knowledge to family members, particularly the husband and wife, to guide the family toward happiness. Faqihuddin presents three key stages in achieving family harmony: the first stage focuses on fulfilling basic physiological needs, such as proper nutrition, rest, and sexual fulfillment; the second stage involves establishing good relationships through principles like mutual acceptance (taraadhin), marriage contracts (mistsaqan galidzan), and effective communication (tasyawur); the third stage highlights reproductive health, including hygiene, pregnancy preparation, and joint responsibility in raising children. This framework offers valuable insights into maintaining a harmonious family life, fostering an environment where every member can thrive.